Microwave spectroscopy of the Yb 6s(n+3)d→6sng, 6snh, and 6sni transitions - F. Niyaz (2019)
© 2019 American Physical Society. Using a microwave and radio frequency resonance approach we observe the transitions of ytterbium from the 6s(n+3)d states to the 6snℓ states for 4≤ℓ≤6 and 28≤n≤33. The energies of the 6snℓ states of ℓ≥4 are determined from the observed intervals and the known values of the 6snd energies. We use a nonadiabatic core polarization model to analyze the energy levels to determine the dipole (αd) and quadrupole (αq) polarizabilities of the ground state of Yb+. We find the values αd=60.51(10)a03 and αq=672(28)a05.